Time-varying transmission between oil and equities in the MENA region: New evidence from DCC-MIDAS analyses - Basel Awartani; Farrukh Javed; Aktham I. Maghyereh; Nader Virk (Review of Development Finance, 2018)
In this paper we use the DCC-MIDAS (Dynamic Conditional Correlation-Mixed Data Sampling) model to infer the association between oil and equities in five MENA countries between February 2006 and April 2017. The model indicates that higher oil returns tends to reduce the long-term risk of the Saudi market, but to increase it in other markets. The risk transfer from oil to MENA equities is found to be weak. The dynamic conditional correlation between oil and equities is not always positive and it unexpectedly changes sign during the sample period. However, the association always strengthens when there is a large draw down in oil prices as well as during periods of high volatility. Finally, we find that short term association occasionally breaks from the longer-term correlation particularly in Egypt and Turkey. These patterns of influence and associations are unique, and have important implications for equity portfolio managers who are interested in investing in energy and MENA equities.
Keywords: G11; G12; G15; 650; GARCH-MIDAS; DCC-MIDAS; Risk transfer; Oil; MENA Equities